Characterization of agarwood incense using gas chromatography – mass spectrometry (GC-MS) coupled with solid phase micro extraction (SPME) and gas chromatography - flame ionization detector (GC-FID) / Nurlaila Ismail … [et al.] - Ismail, Nurlaila; Ibrahim, Mastura; Zareen, Seema; Rahiman, Mohd Hezri Fazalul; Tajuddin, Saiful Nizam; Taib, Mohd Nasir (Institute of Research Management and Innovation (IRMI), 2015)
This paper presents the application of Solid Phase Micro Extraction (SPME) coupled with Gas Chromatography-Mass Spectrometry (GC-MS) and Gas Chromatography-Flame Ionization Detector (GC-FID) to characterize agarwood incense. The work involved three types of SPME fibres at 30 minutes sampling time. The fibres are 50/30 jum divinylbenzene-carboxenpolydimethysiloxane (DVB-CAR-PDMS), 65 jum polydi methylsiloxanedivinylbenzene (PDMS-DVB) and 85 jum carboxen-polydimethyl siloxane (CAR-PDMS). The results showed that among many compounds extracted by GC-MS coupled with SPME, six compounds were found significantly presence in high quality agarwood incense due to their high percentage area (%). They are (5-maaliene, ᵝ-elemol, ᵝ-selinene, 10-epi-y-eudesmol, agarospirol and caryophellene oxide. The finding offers a new approach for establishing the volatile profile of agarwood incense components which is beneficial for agarwood grading and discrimination.